2009
DOI: 10.1002/ajpa.21021
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic evidence for diet at the Imperial Roman coastal site of Velia (1st and 2nd Centuries AD) in Southern Italy

Abstract: Here we report on a stable isotope palaeodietary study of a Imperial Roman population interred near the port of Velia in Southern Italy during the 1st and 2nd centuries AD. Carbon and nitrogen stable isotope analyses were performed on collagen extracted from 117 adult humans as well as a range of fauna to reconstruct individual dietary histories. For the majority of individuals, we found that stable isotope data were consistent with a diet high in cereals, with relatively modest contributions of meat and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
117
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 52 publications
13
117
0
1
Order By: Relevance
“…The minor contribution of marine protein could be emphasised in δ 15 N over δ 13 C coll , recalling that the latter will to some degree reflect carbohydrates and lipids as well as proteins (cf. Craig et al 2009). Ovicaprids are the most important animals in Islamic period diets, but they show a wide range of δ 15 N values, and would be highest for the culturally favoured suckling lamb and kid due to the nursing effect.…”
Section: Discussionmentioning
confidence: 99%
“…The minor contribution of marine protein could be emphasised in δ 15 N over δ 13 C coll , recalling that the latter will to some degree reflect carbohydrates and lipids as well as proteins (cf. Craig et al 2009). Ovicaprids are the most important animals in Islamic period diets, but they show a wide range of δ 15 N values, and would be highest for the culturally favoured suckling lamb and kid due to the nursing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the carbon (δ 13 C co ) and nitrogen (δ 15 N) isotopic ratios of bone collagen is a well-established technique for reconstruction of ancient diets (Bogaard et al, 2007;Craig et al, 2009;Keenleyside et al, 2009). Carbon isotope values can be used to distinguish plants using the C 3 and C 4 photosynthetic pathways and the individuals consuming these plants (Budd et al, 2013;Chenery et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Isotope studies from throughout Italy have demonstrated the dietary breadth of the Empire. For example, Romans at Velia consumed a higher proportion of cereals (Craig et al 2009), whereas those at Isola Sacra likely consumed more marine foods than other areas (Prowse et al 2004) and those at St. Callixtus consumed a higher proportion of freshwater resources (Rutgers et al 2009).…”
Section: Celiac Disease Inferred From Ancient Dnamentioning
confidence: 99%